Compare the Role of 5% Phenol in Almond Oil and Injection Sodium Tetradecyl Sulfate in the Treatment of Rectal Prolapse - Javed Iqbal, Arshad Kamal, Suresh Kumar, Abid Rafiq Chaudhry, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the role of 5% Phenol in Almond oil and Injection Sodium Tetradecyl Sulfate in the treatment of rectal prolapse. Methods and material: This study was conducted at Pediatric Surgery Department, Mayo Hospital Lahore. A total of 100 patients were included in the study and randomly divided into 2 groups. In Group-A patients were given 5% Phenol in Almond Oil and in Group-B patients were given Sodium Tetradecyl Sulfate. Patients were followed up at 1st post operative day and at 1st post operative month to see recurrence or any other complications (bleeding, perirectal inflammation, urinary retention, ischiorectal abscess, and necrosis of the rectal mucosa) in cases in both treatment groups. Results: In Group-A mean age was 5.63±3.34 years and in Group-B mean age of children was 7.16±2.80 years. In Group-A 46 and in Group-B 39 children were included.. There was significant association between treatment groups and outcome on 1st postoperative day reduction (P < 0.05). In Group-A 5 and in Group-B 1 child had bleeding PR after postoperative day. No statistically significant association was present between treatment groups and bleeding PR after POD (P > 0.05). In Group-A 49 and in Group-B 44 children had achieved reduction when observed at one month follow up time period. In Group-A reduction was achieved in greater number of patients as compared to that of Group-B patients (P < 0.05). Practical implication: Current study will bring a revolution in the awareness of community amoung rectal prolapse problem and treating it successfully with the knowledge provided with the current literature. The role of 5% Phenol in Almond oil and Injection Sodium Tetradecyl Sulfate is well shown which proven to be a good treatement in Rectal prolapse. Conclusion: We conclude that 5% Phenol almond oil is more effective than Sodium Tetradecyl Sulfate in treating rectal prolepses. i.e., after the one-month follow-up, the post-operative decrease was 98% vs. 88 percent. Keywords: Rectal submucosa, ischiorectal abscess, ulceration, polyps, inflammation, idiopathic rectal prolapse,Etiology.